The Effect of Exchange Rates on Agricultural Goods for Export: A Case of Thailand - Tulasombat, Sirikul; ., Somchai Ratanakomut (Information Management and Business Review, 2015)
This paper examined the relationships between exchange rates and the volumes of Thailand’s top two majors agricultural goods export which were rice and rubber exports. The results indicated that exchange rates had negative significant effects on Thailand’s agricultural goods export volumes. Results also showed that the exchange rates influenced total agricultural, rubber, and rice goods export volumes respectively. For the qualitative research, interviewing 17 business men who came from rice exports companies 6 persons and from rubber exports companies 11 persons used the in-depth interview. The results showed the effect of exchange rate had strong fluctuation then exporters could not handle it on time, and make the problems all parts of working in companies. Moreover, the best way to do hedging exchange rate risk for exporters, Companies had to book the forward contact in order to reduce the risk.